A hillside of roses : with an annotated and illustrated list of Alister Clark roses - Irvine, Susan, 1928- (Flemington, Vic. : Hyland House, 2007)
"Growing roses in Australia and establishing rose gardens"-- Provided by publisher.
First published: South Yarra, Vic. : Hyland House, 1994.
Includes index.
Bibliography: p. 155-156.
Keywords: Clark, Alister, -- 1864-1949; Rose gardens -- Australia; Rose culture -- Australia; Roses -- Varieties